A Key Ingredient in Deforestation Slowdowns? A Strong Brazilian Economy - Richards, Peter (Frontiers in Forests and Global Change, 2021)
For much of the past two decades, the scientific and policy community has sought to reduce forest loss through well-targeted public policy and enforcement measures and private sector engagement. Unfortunately, recent increases in forest loss in the Amazon have raised new concerns over the drivers of deforestation in the region, and the durability of the policies designed to mitigate it. Here we argue that recent deforestation trends are a partial reflection of Brazil's economic trajectories. In this article we show that poor economic conditions, nationally, will increase micro-level incentives for forest clearing. Conversely, economic growth, nationally, will suppress prices and land clearing incentives. Ultimately, we argue that, at the national-scale, economic growth may be closely aligned with, and possibly a pre-condition to, the attainment of international or national-level environmental goals.